Adoption of Web 2.0 tools among STM publishers. How social are scientific journals? (Journal of EAHIL, 2015)
The use of social media has increased dramatically among scientific researchers, due to their free availability and ease of use. Consequently, publishers have now embraced Web 2.0 features to promote and share the content of their publications and to enhance their visibility and use, as these Web tools are a powerful marketing and promotion channel. Publishers also aim to create a closer relationship with their audience by providing tools to facilitate communication between users of their platforms. Due to the rapid evolution of Web 2.0 technologies, there is little data available on the adoption of these tools among publishers. The purpose of this study is to examine the availability of social media tools by science publishers.